2021
DOI: 10.1177/09596836211041730
|View full text |Cite
|
Sign up to set email alerts
|

Climate and human induced 2000-year vegetation diversity change in Yunnan, southwestern China

Abstract: Understanding long-term vegetation diversity patterns and their potential responses to climate and/or human driven processes are important for ecosystem modeling and conservation. Late-Holocene fossil pollen assemblage and associated vegetation diversity estimates provide an opportunity to explore the interactions among vegetation, climate, and human activities. A continuous 2000-year palynological record was obtained from the Beihai Wetland, southwestern China, to represent regional vegetation history, partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 105 publications
0
0
0
Order By: Relevance
“…At this substage, the Lake Erhai basin was governed by separate tribes and Yunnan had a low population (Figure 9h,i) [60,61], implying the least impact on vegetation from human activities over the last 1640 years. Less human-induced impact on vegetation at this substage was also revealed by pollen records from Lakes Erhai [12], Tiancai [22], Tengchong Qinghai [24,62,63], Lugu [64], and Xingyun [15] as well as the Beihai wetland [8,65] in Yunnan. The Lake Haixihai catchment witnessed the densest vegetation consisting of more pine and hemlock forests and less evergreen broadleaved forests at substage III-2, when both regional temperatures and precipitation underwent a process of dropping, lower than the present, and rising to higher than the present although they did not change in completely synchronous way.…”
Section: Vegetation Succession and Forest Fires Driven By Both Natura...mentioning
confidence: 54%
See 1 more Smart Citation
“…At this substage, the Lake Erhai basin was governed by separate tribes and Yunnan had a low population (Figure 9h,i) [60,61], implying the least impact on vegetation from human activities over the last 1640 years. Less human-induced impact on vegetation at this substage was also revealed by pollen records from Lakes Erhai [12], Tiancai [22], Tengchong Qinghai [24,62,63], Lugu [64], and Xingyun [15] as well as the Beihai wetland [8,65] in Yunnan. The Lake Haixihai catchment witnessed the densest vegetation consisting of more pine and hemlock forests and less evergreen broadleaved forests at substage III-2, when both regional temperatures and precipitation underwent a process of dropping, lower than the present, and rising to higher than the present although they did not change in completely synchronous way.…”
Section: Vegetation Succession and Forest Fires Driven By Both Natura...mentioning
confidence: 54%
“…Environmental changes involve vegetation or land cover change and fire or biomass burning variability. Previous studies have shown that spatial and temporal patterns of vegetation and fire driven by natural and anthropogenic forcings are significantly different on various spatial scales in the world, China, and even Yunnan over the last two millennia [5][6][7][8]. Obviously, more records are needed to develop a detailed picture of regional vegetation changes and fire regimes so that we may understand their global temporal and spatial patterns and dominant driving forcings over the last two millennia.…”
Section: Introductionmentioning
confidence: 99%
“…Debouk et al (2015) emphasized the significance of comprehending the reaction of community plant functional traits to rising temperatures and their contribution to the stability of vegetation. The study conducted by Wang et al 2021) demonstrates a substantial association between changes in vegetation diversity and fluctuations in climate, suggesting a climate-dominant condition.…”
Section: Condition and Potential Of Vegetation In Tambun Selatan Dist...mentioning
confidence: 93%